MAMA Decoction, Nigerian Herbal Antimalarial Preparation, Alters the Disposition of Amodiaquine in Healthy Humans (Nigerian Journal of Pharmaceutical Research, 2024)
Background: MAMA Decoction (MD) is prepared from the leaves of Mangifera indica, Alstonia boonei, Morinda lucida and Azadirachta indica. A co-administration of MD with amodiaquine led to synergism in the clearance of malaria parasites in a previous report. The pharmacokinetic basis for this observation was the subject of another study in mice which found significant MD-induced increase in the exposure and half-life of desethylamodiaquine, the major metabolite of amodiaquine.Objective: This study aimed at evaluating previously identified murine herb-drug interactions in healthy human volunteers.Materials and Methods: Single oral doses of amodiaquine (10 mg/kg) with/without MD (120 mg/kg) were co-administered to 16 healthy subjects in a three-period crossover design. Five millilitres of blood samples were collected employing sparse sampling from 0.25, 0.5, 1, 2, 4, 8, 12, 24 and 48 h postdose, for each study period and analysed for amodiaquine and desethylamodiaquine contents. The effect of MD on amodiaquine disposition across study periods was investigated using a non-linear mixed-effect pharmacokinetic model which estimated population parameters with the stochastic approximation expectation maximization algorithm implemented in Monolix 2020R1.Results: The disposition of amodiaquine and desethylamodiaquine was each described, adequately, by two- and one-compartment structural models respectively, and a first-order oral absorption rate. The co-administration of amodiaquine with MD resulted in about 41% decrease in the apparent volume of distribution of amodiaquine (VAQ/F). Pre-administration of MD prior to amodiaquine led to a 22% decrease in VAQ/F.Conclusion: MAMA decoction appeared to decrease the tissue partitioning of amodiaquine in man. The consequence of this on effective parasite clearance in man is, not yet understood.